2019
DOI: 10.2460/ajvr.80.9.840
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the radiographic cardiac silhouette of ospreys (Pandion haliaetus)

Abstract: OBJECTIVE To evaluate and report measurements of the radiographic cardiac silhouette of healthy juvenile and adult ospreys (Pandion haliaetus). ANIMALS 54 ospreys (22 adults, 19 juveniles, and 13 birds of undetermined age) without clinical signs of cardiac disease and with adequate ventrodorsal radiographic images for cardiac silhouette assessment. PROCEDURES Radiographs of ospreys were assessed to determine cardiac width at the widest point as well as sternal width and thoracic width at the same level. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…In laying hens, as previously described, egg position was observed to rotate. 15 However, no specific pattern could be identified in the present study. These rotations were observed at different times and not in all chickens, with the blunt end of the egg often found cranially (as described) but sometimes caudally too.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…In laying hens, as previously described, egg position was observed to rotate. 15 However, no specific pattern could be identified in the present study. These rotations were observed at different times and not in all chickens, with the blunt end of the egg often found cranially (as described) but sometimes caudally too.…”
Section: Discussioncontrasting
confidence: 70%
“…Interestingly, this pattern is the exact opposite of the evolution of eggshell density evaluated radiographically in another chicken study. 15 It appears that in our group of laying hens that approximately 5 hours after oviposition the calcium deposition starts on the next egg, with a rapid increase in the eggshell thickness for the first 5 hours that is followed by an increase in the density of the eggshell. This study also showed that if the laying time is not known in a given hen, it can be approximated by measuring eggshell thickness, if present.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…To improve the accuracy of the diagnosis, many studies have attempted to establish reference values of the cardiac silhouette in different avian species, including African grey parrots (Psittacus erithacus), Senegal parrots (Poicephalus senegalus), orange-winged Amazon parrots (Amazona amazonica), blue-fronted Amazon parrots (Amazona aestiva), budgerigars (Melopsittacus undulatus), Spix's macaws (Cyanopsitta spixii), peregrine falcons (Falco peregrinus), Harris's hawks (Parabuteo unicinctus), saker falcons (Falco cherrug), lanner falcons (Falco biarmicus), red-tailed hawks (Buteo jamaicensis), bald eagles (Haliaeetus leucocephalus), ospreys (Pandion haliaetus), screech owls (Otus asio), Canada geese (Branta canadensis), common kestrels (Falco tinnunculus), Bonelli's eagles (Aquila fasciata), and Humboldt penguins (Spheniscus humboldti) [4][5][6][7][8][9][10][11][12][13][14][15]. The correlations measured between the heart size and stable points in the body could be used to direct the practitioner and identify alterations in heart size.…”
Section: Introductionmentioning
confidence: 99%